Legal Liability for the Bankruptcy of a Limited Liability Company Resulting from Unlawful Conduct - Laksana, Angelia; Margaret, Felicia; Pradigdo, Yolanda Yuliani; Wuwung, Ivana Cindi Lydia (Journal of Law, Politic and Humanities, 2025)
Abstract: This study explores the legal liability of a limited liability company in the event of bankruptcy arising from unlawful acts committed by its management or controlling parties. The research aims to analyse the extent to which corporate liability can be imposed under Indonesian company law, bankruptcy law, and civil law principles, particularly when the principle of limited liability is challenged by fraudulent or unlawful conduct. Using a normative juridical method, this study examines primary legal sources, including the Indonesian Civil Code, Law No. 40 of 2007 concerning Limited Liability Companies, and Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. Secondary legal materials, such as books, journal articles, and legal commentaries, are also analysed to provide theoretical support and comparative perspectives. The findings suggest that although the doctrine of separate legal personality protects shareholders from personal liability, exceptions may apply when unlawful acts such as fraud, bad faith, or abuse of corporate structure occur, thereby justifying the piercing of the corporate veil. This study highlights the importance of balancing legal certainty with fairness and accountability in corporate bankruptcy cases which offers recommendations that strengthen creditor protection and ensure directors cannot evade responsibility through corporate formalities. Keyword: limited liability company, bankruptcy, legal liability, unlawful conduct